Golfing after Orthopaedic Surgery: A longitudinal follow-up (GOLF) study protocol - Patrick G. Robinson; Andrew P. Creighton; Jennifer Cheng; Joshua S. Dines; Edwin P. Su; Lawrence V. Gulotta; Douglas Padgett; Constantine Demetracopoulos; Roger Hawkes; Heidi Prather; Joel M. Press; Nick D. Clement (Bone & Joint Open, 2023)
Aims: The primary aim of this prospective, multicentre study is to describe the rates of returning to golf following hip, knee, ankle, and shoulder arthroplasty in an active golfing population. Secondary aims will include determining the timing of return to golf, changes in ability, handicap, and mobility, and assessing joint-specific and health-related outcomes following surgery. Methods: This is a multicentre, prospective, longitudinal study between the Hospital for Special Surgery, (New York City, New York, USA) and Edinburgh Orthopaedics, Royal Infirmary of Edinburgh, (Edinburgh, UK). Both centres are high-volume arthroplasty centres, specializing in upper and lower limb arthroplasty. Patients undergoing hip, knee, ankle, or shoulder arthroplasty at either centre, and who report being golfers prior to arthroplasty, will be included. Patient-reported outcome measures will be obtained at six weeks, three months, six months, and 12 months. A two-year period of recruitment will be undertaken of arthroplasty patients at both sites. Conclusion: The results of this prospective study will provide clinicians with accurate data to deliver to patients with regard to the likelihood of return to golf and timing of when they can expect to return to golf following their hip, knee, ankle, or shoulder arthroplasty, as well as their joint-specific functional outcomes. This will help patients to manage their postoperative expectations and plan their postoperative recovery pathway. Cite this article: Bone Jt Open 2023;4(7):490–495.